Potential of MODFLOW to model hydrological interactions in a Semikarst floodplain of the Ozark Border Forest in the Central United States - Chinnasamy, Pennan; Hubbart, J.A. (American Meteorological Society, 2014)
Riparian shallow groundwater and nutrient movement is important for aquatic and forest ecosystem health. Understanding stream water (SW)–shallow groundwater (GW) interactions is necessary for proper management of floodplain biodiversity, but it is particularly confounding in underrepresented semikarst hydrogeological systems. The Modular Three-Dimensional Finite-Difference Ground-Water Flow Model (MODFLOW) was used to simulate shallow groundwater flow and nutrient transport processes in a second-growth Ozark border forest for the 2011 water year. MODFLOW provided approximations of hydrologic head that were statistically comparable to observed data (Nash–Sutcliffe = 0.47, r2 = 0.77, root-mean-square error = 0.61 cm, and mean difference = 0.46 cm). Average annual flow estimates indicated that 82% of the reach length was a losing stream, while the remaining 18% was gaining. The reach lost more water to the GW during summer (2405 m3 day-1) relative to fall (2184 m3 day-1), spring (2102 m3 day-1), and winter (1549 m3 day-1) seasons. Model results showed that the shallow aquifer had the highest nitrate loading during the winter season (707 kg day-1). A Particle-Tracking Model for MODFLOW (MODPATH) revealed significant spatial variations between piezometer sites (p = 0.089) in subsurface flow path and travel time, ranging from 213 m and 3.6 yr to 197 m and 11.6 yr. The current study approach is novel with regard to the use of transient flow conditions (as opposed to steady state conditions) in underrepresented semikarst geological systems of the U.S. Midwest. This study emphasizes the significance of semikarst geology in regulating SW–GW hydrologic and nutrient interactions and provides baseline information and modeling predictions that will facilitate future studies and management plans.